A novel treatment for an 8-year-old pulpectomy patient followed by the placement of Bioflx crowns: a case report - Paham, Anindya Larasati; Gartika, Meirina (Universitas Padjadjaran, 2025)
Introduction: Pulpectomy is a common treatment for primary teeth affected by irreversible pulpitis or pulp necrosis, with the goal of preserving their function and condition until natural exfoliation occurs. Successful outcomes depend not only on effective canal debridement but also on the selection of an appropriate final restoration. Bioflx crowns are a newly introduced full-coverage restoration that offers both aesthetic and functional benefits, making them suitable for pediatric patients. This case report presents a novel treatment for an 8-year-old patient who underwent a pulpectomy, followed by the placement of Bioflx crowns. Case Report: An 8-year-old girl complained of persistent pain in her lower left posterior tooth for the past two weeks. Clinical and radiographic examination confirmed a diagnosis of pulp necrosis in tooth #75. The treatment plan included pulpectomy followed by Bioflx crown placement, based on parental preference for a durable and aesthetic solution. This case highlights the application of a flexible hybrid polymer crown in a post-endodontic primary molar-an approach rarely reported. The report provides a comprehensive account of the clinical procedure and short-term outcomes. At each visit, favorable healing was observed, with no discomfort or signs of reinfection. After one month of follow-up, radiographic evaluation confirmed adequate obturation and crown margin adaptation. Conclusion: Bioflx crowns demonstrated clinical effectiveness as a restorative option following pulpectomy in pediatric patients, with excellent marginal integrity, retention, and aesthetics observed during follow-up.